2017
DOI: 10.1038/nature24633
|View full text |Cite
|
Sign up to set email alerts
|

Origin and differentiation of human memory CD8 T cells after vaccination

Abstract: The differentiation of human memory CD8 T cells is not well understood. Here we address this issue using the live yellow fever virus (YFV) vaccine, which induces long-term immunity in humans. We used in vivo deuterium labelling to mark CD8 T cells that proliferated in response to the virus and then assessed cellular turnover and longevity by quantifying deuterium dilution kinetics in YFV-specific CD8 T cells using mass spectrometry. This longitudinal analysis showed that the memory pool originates from CD8 T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
505
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(545 citation statements)
references
References 33 publications
39
505
0
1
Order By: Relevance
“…Further links between metabolism and epigenetic regulation of immune cells are beginning to emerge . Recent studies in mice and humans provide evidence that suggests memory T cells arise from effector T‐cell memory precursor pools and can retain an effector like epigenetic signature . This supports the concept that that memory T‐cell differentiation could be linked with epigenetic modifications at specific loci and that these cells are epigenetically poised to respond to secondary stimulation.…”
Section: Metabolic Signaling and Epigenetics In Memory T Cellsmentioning
confidence: 80%
“…Further links between metabolism and epigenetic regulation of immune cells are beginning to emerge . Recent studies in mice and humans provide evidence that suggests memory T cells arise from effector T‐cell memory precursor pools and can retain an effector like epigenetic signature . This supports the concept that that memory T‐cell differentiation could be linked with epigenetic modifications at specific loci and that these cells are epigenetically poised to respond to secondary stimulation.…”
Section: Metabolic Signaling and Epigenetics In Memory T Cellsmentioning
confidence: 80%
“…Since all these memory T cells share the same phenotypic markers, the lifespan of each of these types of memory cells remained unknown. Recently, Akondy et al reported on a long‐term deuterium‐labeling study to investigate the dynamics of cognate memory T cells in volunteers vaccinated against yellow fever (YF). The investigators were able to determine the deuterium enrichment in a relatively small CD8 + memory tetramer + T‐cell pool specific for this virus.…”
Section: Memory T‐cell Dynamics In Humans and Micementioning
confidence: 99%
“…A major new finding was that—despite the average lifespan of YV‐specific memory T cells of about 4 months—a large population of labeled memory cells persisted for years after vaccination, and that these persisting cells had a quiescent phenotype with features of stem‐cell‐like and effector‐like memory CD8 + T cells . The latter finding suggests that either CD8 + memory T cells slowly increase their longevity by becoming more quiescent over time, or that the population of antigen‐specific CD8 + memory T cells is kinetically heterogeneous, with the most quiescent subset becoming more predominant over time because they survive longer . Another major new finding was that YV‐specific memory cells had a very long intermitotic interval of 1/0.0015=666 days, that is, longer than their life expectancy.…”
Section: Memory T‐cell Dynamics In Humans and Micementioning
confidence: 99%
“…4 Although long-lasting debates have been focused on the identity of memory precursors and the differentiation path of memory T cells, 5 recent works have provided solid epigenetic evidence that virus-specific memory T cells transit through an effector stage, not directly derive from naïve cells in both mouse and human. 6,7 …”
Section: Introductionmentioning
confidence: 99%